Micronutrients and macronutrients in poultry feed supplemented with mussel meat and mussel shell - Lee, Nian Yian, 1987-; Hanim Awab, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010